Assessment of SLEDAI Score in Children with Lupus Nephritis Class III-IV in Vietnam National Children’s Hospital - Thi Thanh Binh, Duong; Thu Huong, Nguyen; Thi Kien, Nguyen; Van Dem, Pham; Minh Dien, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2020)
This study describes clinical, paraclinical characteristics and treatment response in children with nephritis class II-IV caused by systemic lupus erythematosus and validates SLEDAI for the evaluation of disease activity and the appropriate treatment strategy. A cross-sectional descriptive study was carried out on 40 children, 37 girls (92%) and 3 boys (8%), with an average age of 11.7 years with lupus nephritis class III- IV in Vietnam National Children’s Hospital in 2019. The study results show that the average score of SLEDAI in the children with pericardial and pleural effusions was 20.94 ± 4.09; high blood pressure, 20.89 ± 4.23; and gross hematuria, 20.29 ± 5.03, which were higher than those in children without these manifestations with p< 0.05. The most common kidney manifestations were nephrotic-range nephritis with renal failure (40%) and Glomerulonephritis (35%), corresponding to an average SLEDAI score of 24.25 ± 5.52 and 24.33 ± 3.2, respectively (p = 0.001). SLEDAI had an inverse correlation with the C3 complement value (r -0.315, p <0.05). The average SLEDAI score decreased gradually from 18.75 ± 4.22 to 3.38 ± 3.95 points (p <0.001) after 12 months of treatment.  The study concludes that SLEDAI score was higher in patients with pleural and/or pericardial effusions, hypertension and gross hematuria, nephrotic-range nephritis with kidney failure or glomerulonephritis. SLEDAI score corresponded with the C3 complement value and the average SLEDAI score decreased gradually with treatment. Keywords: Lupus Nephritis class III- IV, SLEDAI. References [1] George Bertsias, Ricard Cervera và Dimitrios T Boumpas, Systemic Lupus Erythematosus: Pathogenesis and Clinical Features<sample chapter 20_mod 17_Systemic Lupus nephritis 2012.pdf> (2012), EULAR Textbook on Rheumatic Diseases, EULAR, 476-505. [2] D.M. Levy and S. Kamphuis, Systemic lupus erythematosus in children and adolescents. Pediatr Clin North Am59(2) (2012)345-64. [3] Thai Thien Nam, 2018, Lupus in National Children,s Hospital, [4] C.Bombardier, M.B. Hurwitz et al, Derivation of the SLEDAI: A disease activity index for lupus patients. The committee on prognosis studies in SLE, Arthritis Rheum 35(6) (1992) 630-640. [5] R. Shamim, S. Farman, S. Batool et al, Association of systemic lupus erythematosus disease activity index score with clinical and laboratory parameters in pediatric onset systemic lupus erythematosus. Pak J Med Sci. 36(3) (2020) 467-472. [6] Le Thuy Hang, Assesment of SLEDAI score and panthology in children with lupus nephritis, 2016, Pediatrician thesis, Hanoi Medical University. [7] S.K.S.M. Nazri, K.K. Wong and W.Z.W.A. Hamid, Pediatric systemic lupus erythematosus. Retrospective analysis of clinico-laboratory parameters and their association with Systemic Lupus Erythematosus Disease Activity Index score, Saudi Med J. 39(6) (2018) 627-631. [8] Nguyen Thuy Duong, clinical, paraclinical and pathology characteristics in children with nephritis caused by systemic lupus erythematosus, 2011, Master thesis, Hanoi Medical University. [9] S.N. Wong, W.K. Chan, J.Hui et al, Membranous lupus nephritis in Chinese children--a case series and review of the literature. Pediatr Nephrol, 24(10)(2009) 1989-1996. [10] N.T.N. Dung, H.T. Loan, S. Nielsen et al, Juvenile systemic lupus erythematosus onset patterns in Vietnamese children: a descriptive study of 45 children. Pediatric Rheumatology Online Journal, 10 (2010) 38-48. [11] T. Pusongchai, J. Jungthirapanich, S. Khositseth, Pediatric Systemic Lupus Erythematosus in Thammasat University Hospital, J Med Assoc Thai. 93(12) (2010) 283-290.